2016
DOI: 10.1186/s13005-016-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus clinical characteristics in Italian patients: a retrospective analysis

Abstract: BackgroundOral lichen Planus (OLP) is a chronic inflammatory disease involving skin and mucous membranes. Its etiology is still uncertain whilst an autoimmune mechanism is known to be implicated. OLP is commonly considered a geriatric disease and gender differences in prevalence are clear, whereby females are generally more frequently affected than males more often during the 5th and 6th decades of life. Lesions are symmetrical and bilateral and the buccal mucosa is frequently involved. The risk of malignant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
8
33
1
Order By: Relevance
“…As other authors had prior (Ingafou, Leao, Porter, & Scully, ; Lauritano et al, ; Mostafa & Ahmed, ; Xue et al, ), we found a higher incidence of OLP in women (85.4%). A possible reason for this association could be that women have greater genetic, neuronal and psychological predisposition to developing depressive or anxious episodes (Ramsey et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As other authors had prior (Ingafou, Leao, Porter, & Scully, ; Lauritano et al, ; Mostafa & Ahmed, ; Xue et al, ), we found a higher incidence of OLP in women (85.4%). A possible reason for this association could be that women have greater genetic, neuronal and psychological predisposition to developing depressive or anxious episodes (Ramsey et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…Even so, reticular lesions are probably the most common, given that they are, in many cases, casual findings, whereas atrophic/ulcerative lesions are a frequent reason for a consultation because of the symptoms they present (Blanco Carrión et al, 2008). Regarding location, the most common lesions were those appearing on the buccal mucosa, both bilaterally and symmetrically, as occurred in other studies (Kaplan et al, 2012;Lauritano et al, 2016;Mostafa & Ahmed, 2015;Shirasuna, 2014;Xue et al, 2005).…”
Section: Discussionmentioning
confidence: 66%
“…6 Diabetes, hypertension, hepatitis C, and thyroiditis have been the most frequently associated systemic diseases with OLP. 27 Our findings are also in accordance with the Pippi et al case-control study which reported significant associations among smoking, psychological factors, and OLP. 28 In the present study, OLP patients as compared to their matched controls more frequently experienced oral disease-related pain or discomfort.…”
Section: Resultssupporting
confidence: 92%
“…It can be noticed clear difference in reported coexistence of thyroid gland pathosis and OLP between Northern and Central European countries (Finland [11], Czech Republic [28] and Croatia [34]) and Southern Mediterranean countries (Italy [1,26] and Turkey [29]). Although, distinction in thyroid gland diseases prevalence is obvious between the different regions of the same country, reported on different sample size [1,31]. These observation and results of present study suggest that the association of thyroid diseases with OLP may depend on the geographic origin of the patients, similar to HCV association [1,7,35].…”
Section: Discussionsupporting
confidence: 63%
“…Eleven of them had histological confirmation of all cases with distinguish between OLP and OLL [1,11,23,25,[27][28][29][30][31][32][33] and five presented with control group [11,13,24,25,27]. It can be noticed clear difference in reported coexistence of thyroid gland pathosis and OLP between Northern and Central European countries (Finland [11], Czech Republic [28] and Croatia [34]) and Southern Mediterranean countries (Italy [1,26] and Turkey [29]).…”
Section: Discussionmentioning
confidence: 99%